Pengembangan Instrumen Penilaian Kemampuan Berpikir Tingkat Tinggi Materi Sistem Pendengaran dan Sonar SMP - Vita Ria Mustikasari; Munzil Munzil; Lia Puji Lestari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The aim of this study is to produce a higher-order thinking skills assessment instrument on the material of the hearing and sonar system for Junior high school students that are valid and reliable. Indicators of higher-order thinking skills (IKBTT) are developed based on the cognitive dimension of Bloom's Taxonomy which includes the skills to analyze (C4), evaluate (C5) and create (C6). The assessment instrument developed was a multiple choice test with open reasons. Multiple choice test with open reason is a multiple choice question with four answer choices completed with the reason for choosing an answer. The instrument is equipped with an assessment rubric in the form of a holistic rubric to assess the relationship between multiple choice answers and reasons for choosing answers. The results of the validation of material aspects, construction, and language show that the products developed are very feasible with an average score of 85.7%. The instrument was empirically tested with the number of subjects trying as many as 59 students of 8th grade Junior high school. Based on the results of empirical trials of multiple choice questions with open reasons obtained 25 valid questions with multiple choice reliability of 0.745, and reason reliability of 0.929. The number of questions produced based on C4 cognitive dimensions were 12 questions (48%), C5 cognitive dimensions were 9 questions (36%), and C6 cognitive dimensions were 4 questions (16%). This study produced an instrument for assessing higher-order thinking skills in the material of the hearing and sonar system for Junior high school students that were valid and reliable.